2009
DOI: 10.1002/eji.200839080
|View full text |Cite
|
Sign up to set email alerts
|

Alternative mRNA splicing creates transcripts encoding soluble proteins from most LILR genes

Abstract: Leucocyte Ig-like receptors (LILR) are a family of innate immune receptors expressed on myeloid and lymphoid cells that influence adaptive immune responses. We identified a common mechanism of alternative mRNA splicing, which generates transcripts that encode soluble protein isoforms of the majority of human LILR. These alternative splice variants lack transmembrane and cytoplasmic encoding regions, due to the transcription of a cryptic stop codon present in an intron 5 0 of the transmembrane encoding exon. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 55 publications
(96 reference statements)
1
31
0
Order By: Relevance
“…SCN1B -dependent regulation of neuronal pathfinding may be critical to abnormal brain development in both neurological and psychological disease. Expression of multiple SCN1B splice variants, including a secreted form, is also consistent with other members of the Ig superfamily of CAMs (Rougon and Hobert 2003; Jones, et al 2009). For example, increased expression of secreted forms of NCAM is associated with bipolar disorder and depression (Brennaman and Maness 2010).…”
Section: Discussionsupporting
confidence: 68%
“…SCN1B -dependent regulation of neuronal pathfinding may be critical to abnormal brain development in both neurological and psychological disease. Expression of multiple SCN1B splice variants, including a secreted form, is also consistent with other members of the Ig superfamily of CAMs (Rougon and Hobert 2003; Jones, et al 2009). For example, increased expression of secreted forms of NCAM is associated with bipolar disorder and depression (Brennaman and Maness 2010).…”
Section: Discussionsupporting
confidence: 68%
“…2C, "Intramembrane Polypeptide Region" [IPR]; Supplemental Table S3). This observation suggests that alternative splicing may impact the ability of proteins to be incorporated into cellular membranes as was reported in a few cases (Stamm et al 2005;Jones et al 2009;Tejedor et al 2015). Even though we do not know yet the biological meaning of the enrichment for some protein features in different exon categories, we believe these data are important to underscore the importance of using an appropriate set of control exons.…”
Section: Enrichment Of Exon Ontology Termsmentioning
confidence: 71%
“…Previous studies have shown that this gene is highly polymorphic (24) and can be alternatively spliced (25). However, a recent genome-wide association study did not reveal a significant association between LILRB1 and dengue shock syndrome (26); this is not surprising because, although LILRB1 activation is critical for initial replication with FcγR-mediated entry, multiple other host and viral factors contribute to eventual disease outcome.…”
Section: Discussionmentioning
confidence: 99%